Atividades leishmanicida e imunomoduladora do óleo essencial e do isolado 6,7-dehidroroileanona derivados de Tetradenia riparia (Hochstetter) Codd - Demarchi, Izabel Galhardo (2015)
Cutaneous leishmaniasis is caused by protozoa of the genus Leishmania, and it is characterized by skin lesions localized or disseminated. Leishmania (Leishmania) amazonensis is responsible agent for cutaneous and diffuse cutaneous, the most severe clinical and difficult to treat form. This species usually shows therapeutic resistance leading to therapy failure and worsening injury. The current treatment for leishmaniasis has caused serious side effects and toxicity. In this context, the natural products are considered potential candidates for alternative therapy for leishmaniasis, as well the leishmanicidal activity, products able to modulate cytokines of the host immune response are essential for the resolution of the disease. The Tetradenia riparia plant is used as traditionally in Africa for the treatment of inflammatory and infectious diseases. The extracts and the essential oil derived from this plant have antioxidant, anticarcinogenic and antimicrobial properties. Although this plant is used as a folk medice in different populations for curing a variety of diseases, few studies have investigated the anti-Leishmania and immunomodulatory effects of the T. riparia plant. The essential oil derived from T. riparia (TREO) is a rich complex of terpenoids, including diterpenes (or oxygenated hydrocarbons) related to the antimicrobial activity of essential oils. The diterpene 6,7-dehidroroileanona derived from T. riparia (TrROY) has recently been described in the literature, there are few studies on the pharmacological properties of this compound. In this study, we investigated: the leishmanicidal potential TrEO and TrROY on promastigotes and amastigotes of L. (L.) amazonensis; the cytotoxicity of TrEO and TrROY on murine macrophages and human erythrocytes; the production of nitrite and nitric oxide synthase mRNA expression (iNOS) by murine macrophages infected with L. (L.) amazonensis and treated with TrEO; the immunomodulation of murine macrophages treated with TrEO; and modulation of gene expression and cytokine production by murine macrophages treated with TrEO and infected with L. (L.) amazonensis. The effects of TrEO and TrROY on Leishmania promastigotes were evaluated using three methods, the conventional microscopic, reduction of XTT (2,3-bis [2-methoxy-4-nitro-5-sulfophenyl]-5-[(phenylamino), and transmission electron microscopy to check the ultrastructural alterations of promastigotes treated with TrEO. The TrEO and TrROY cytotoxicity was evaluated using the XTT method and Trypan Blue exclusion test, and for human erythrocytes was performed hemolysis test from reading in spectrophotometer. To check the effects of TrEO and TrROY on intracellular forms of Leishmania, peritoneal macrophages obtained from BALB/c mice were infected with promastigotes, and subsequently treated with TrEO and TrROY. The percentage of infected cells and the average number of amastigotes per macrophage was obtained counting cells in conventional light microscopy. Quantitative real time polymerase chain reaction (qPCR) was also performed to determine the quantity of parasites based on the Leishmania DNA detection. For studies of immunomodulation, murine peritoneal macrophages were infected with Leishmania, and treated with 30 ng/mL of TrEO. After 3, 6 and 24 hours of incubation, nitrite production was determined by spectrometry using the Griess reagent, and expression of iNOS and cytokines (interleukins, IL-1β, IL -2, IL-4, IL-5, IL-6, IL-10, IL-12, IL-17, IL- 18, IL-33, interferon-γ, IFN-γ, tumor necrosis factor, TNF; growth factor of colonies of granulocytes and macrophages, GM-CSF) was measured by semi-quantitative PCR method associated with the reverse transcriptase. Cytokine production was detected by flow cytometry. For statistical analysis it was considered a 95% confidence interval. TrEO and TrROY promote the L. (L.) amazonensis promastigote forms death within 72 h of incubation. TrEO was more effective than TrROY, which the 50% lethal dose (LD50) of TrEO was 0.8 μg/mL and TrROY 3 μg/mL. TrEO and TrROY did not show cytotoxicity on human erythrocytes, but TrROY showed toxicity to murine macrophages resulting in a low selectivity index. TrEO at the concentration of 0.03 μg/mL was able to modify the ultrastructures of the promastigotes suggesting autophagy process and cell death indicated by the presence of chromatin condensation, membrane blebbing formation, membranous profiles and nuclear fragmentation. Macrophages treated with 0.03 μg/mL of TrEO and 10 μg/ml of TrROY reduced the infection index from 177 (macrophages infected with Leishmania) to 65 and 48%, respectively. TrEO and TrROY subvert the inhibition of expression of iNOS and nitrite production in macrophages infected with Leishmania. TrEO modulated cytokine gene expression and synthesis by murine macrophage uninfected and treated in all periods studied. The modulation of gene expression occurred only at 3 and 6 h, while the effects on cytokine production were observed up to 24 h. The expression and production 1β, IL-12, IL-17 and IFN-γ were highly induced by TrEO at 3 h. IL-1β was expressed and produced in high levels in 6 h, which was gradually reduced to the period of 24 h. IL-2 was produced at high levels at the start of incubation, and GM-CSF and IL-17 later (24 h). TrEO significantly inhibited IL- 10 and IL-6 production by murine macrophages. In macrophages infected with Leishmania, and treated with TrEO, IFN-γ was highly produced, and IL-1β, IL-6, IL-17, IL-33, TNF, and TH2-type cytokine response (helper T lymphocytes, IL-4, IL-5 and IL-10) were inhibited. IL- 12 levels were maintained at normal levels by treatment with TrEO. While infection with L. (L.) amazonensis stimulated IL-10 production, IL-1β, IL-4, IL-5, IL-6, IL-17 and IL-33, and inhibit IL-12 and IFN-γ produced by macrophages infected and not treated, TrEO treatment subvert it favoring the infection resolution. TrEO and TrROY promote the death of L. (L.) amazonensis possibly by mitochondrial, respiratory and lipid metabolism. TrEO at low concentrations did not show cytotoxicity to cells and is capable of modulating gene expression and production of major cytokines of the immune response. The profile of cytokines induced by TrEO in the absence of infection is associated with stimulation of the innate cellular immune response and suppression of TH2 cell cytokines. Thus, TREO would be an alternative therapy for various diseases in which the immune response is crucial for its resolution as in infectious diseases, autoimmune and cancer. The effects of TrEO on leishmaniasis, suggests that it is able to suppress TH2 cytokines involved with the progression of leishmaniasis, and enhances IFN-γ which is essential for the resolution of this disease. All these results support the use of T. riparia plant as a folk medicine for the treatment of parasitic infections such as leishmaniasis and other diseases which require modulation of the immune response. TrEO could be used as an alternative therapy for leishmaniasis. We suggested that in vivo tests in humans are performed to ensure its efficacy and safe use of this treatment for leishmaniasis or other disease.